Analysis of the Determinants of Open Unemployment Rate: The Role of Human Development Index and Socioeconomic Factors - Apriyanti, Cikit; Yanuarti, Mira (Institute Of Advanced Knowledge and Science, 2024)
Economic conditions, unfavorable government policies, the growth of fictitious economic sectors, a lack of education and skills, a shortage of employment opportunities relative to the number of job seekers, and job seeker competencies that do not align with the job market are some of the factors that contribute to unemployment. Analyzing the main determinants of the open unemployment rate in Bengkulu Province is the aim of this study. Multiple linear regression analysis was employed in this work to analyze secondary data from 2012 to 2023 that was obtained from the Bengkulu Province BPS. The study's findings demonstrated that the F count value of 3.391 from the simultaneous test was higher than the F table value of 3.106. The dependent and independent variables are not influenced by one another, it can be concluded. With a significance value of 0.195>0.05, the Human Development Index (HDI) (X4) is the variable that most affects the open unemployment rate in the partial test. It has a positive impact on the open unemployment rate. With a computed t value of 1.433 and a t table of 1.39682, the Human Development Index (HDI) (X4) is the variable that most affects the Open Unemployment Rate. The Determination Coefficient is 0.655, meaning that the Human Development Index (HDI) (X4), Population (X2), Poverty (X3), and PDRB (X1) each contributed 65.5% and 34.5%, respectively.